Kasus Dana Zakat Tidak Tepat Sasaran di Baznas Cilegon : Analisis Amanah dan Pertanggungjawaban dalam Islam - Usi Fauziyah; Muhammad Fadhlan; Dandi Ganjar Irawan; Lina Marlina (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study explores the issue of misallocated zakat distribution at BAZNAS Cilegon, emphasizing the significance of trustworthiness (amanah) and accountability within the Islamic framework. Zakat serves not only as an act of worship but also as a socio-economic instrument designed to reduce inequality and improve community welfare. However, in practice, its distribution often encounters obstacles, particularly regarding transparency and the accuracy of targeting beneficiaries. Employing a qualitative approach with a library research method, this study analyzes scholarly journals, books, and official reports relevant to the topic. The findings reveal that weak beneficiary data collection, insufficient verification processes, and limited monitoring mechanisms contribute to zakat being distributed to unintended recipients. The suspected misuse of zakat funds at BAZNAS Cilegon highlights the urgent need for trustworthy and transparent governance supported by modern management systems. The implications of this study suggest that strengthening monitoring systems, implementing regular sharia-based audits, utilizing digital technology for data integration, and enforcing strict sanctions against negligent or dishonest amil are crucial steps to rebuild public trust. Ultimately, zakat can only achieve its dual function as a form of worship and as an instrument of social justice when managed with integrity, transparency, and professionalism.